Kurikulum Merdeka: Kendala dalam Pembelajaran di Sekolah - Rizki, Aptania; Putri, Sella Ayu Eka (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to identify obstacles in the implementation of the Independent Curriculum in the subject of fine arts for grade 1 at MI Plus Nur Rahma, Bengkulu City. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation of teachers, students, principals, and curriculum vice principals. The results of the study indicate that although the Independent Curriculum has been implemented in accordance with government policy, its implementation is faced with a number of significant obstacles. Teachers have difficulty in understanding and designing appropriate teaching tools, especially in compiling fine arts teaching modules that are relevant to the characteristics of students. Limited training and mentoring cause teachers to still be trapped in the lecture method and are less able to apply differentiated learning which is the core of the Independent Curriculum. Students also show low active participation in learning due to methods that are not yet student-centered. In addition, the lack of facilities and infrastructure and the lack of teacher understanding of the use of technology also exacerbate these conditions. These findings provide a real picture of the challenges at the education unit level in implementing curriculum reform and the importance of continuously improving teacher capacity.